The Charismatic Gymnasium : Breath, Media, and Religious Revivalism in Contemporary Brazil - Abreu, Maria Jose de, 1970- (Book collections on Project MUSE., 2021)
"Maria Jose A. de Abreu examines the conservative Charismatic Catholic movement in contemporary urban Brazil to rethink the relationship between theology, the body, and neoliberal governance, showing how it works to produce subjects who are complicit with Brazilian neoliberalism."--